Analysis of a Singly-Fed Circularly Polarized Electromagnetically Coupled Patch Antenna - Hajiaboli, A.; Popović, M. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
This paper presents analysis of a broadband circularly polarized electromagnetically coupled patch antenna (EMCP) fed thorough a coaxial probe. The bandwidth of the antenna is investigated numerically and through experiment. The 12% bandwidth of the measured return loss implies broadband behavior considering the operating frequency and the inherent bandwidth limitations of the microstrip antenna structure. The changes in circular polarization bandwidth were investigated using finite-element-method (FEM) software and the results suggest that the increase in separation between the patches causes a decrease of 3dB bandwidth and the degradation of the minimum value of axial ratio. An axial ratio bandwidth of 2% is achieved in the reported EMCP structure. In addition, we have applied a modal analysis using finite-difference time-domain (FDTD) simulation to reveal the simultaneous excitation of TM01 and TM10 modes at around 1.3GHz. These results help explain the broadband and circular polarization characteristics of the EMCP structure under investigation.